Exploring the relationship between dispositions to think critically and sustainability concern in HESD. Issue 5 (17th June 2021) - Shephard, Kerry; Kalsoom, Qudsia; Gupta, Ritika; Probst, Lorenz; Gannon, Paul; Santhakumar, V.; Ndukwe, Ifeanyi Glory; Jowett, Tim
Abstract : Purpose: Higher education is uncertain which sustainability-related education targets should be sought and monitored. Accepting that something needs to be measurable to be systematically improved, the authors explored how measures relate to potential targets. This paper aims to focus on dispositions to think critically (active open-minded thinking and fair-minded thinking in appraising reasoning) as measures and explored how they related to sustainability concern as an indicative educational target. Design/methodology/approach: This research included the development and testing of research instruments (scales) that explored dispositions to critical thinking and sustainability concern. Authors researched these instruments within their own correspondence groups and tested them with university students and staff in Pakistan, the USA, Austria, India and New Zealand. The authors also asked a range of contextualising questions. Findings: Respondents' disposition to aspects of active, open-minded thinking and fair-minded thinking do predict their concern about facets of sustainability but their strength of religious belief was an important factor in these relationships and in their measurement. Practical implications: This research demonstrates the complexity of monitoring dispositions to think critically and sustainability concern in educational systems, particularly in circumstances where the roles of religious beliefs are of interest; and suggests ways to address this complexity. Originality/value: This research integrates and expands discourses on ESD and on critical thinking in diverse disciplines and cultures. It investigates measurement approaches and targets that could help higher education institutions to educate for sustainable development and to monitor their progress, in ways that are compatible with their culture and values.